Thermal and mechanical performance of geopolymer concrete with recycled aggregate and copper slag as fine aggregate - Anasuya Sahu; Pramod Kumar; Bheem Pratap; Abhilash Gogineni; Regasa Yadeta Sembeta (Scientific Reports)
Abstract This study investigates the thermal and mechanical performance of geopolymer concrete incorporating recycled coarse aggregate (RCA) and copper slag (CS) as sustainable alternatives to natural aggregates. The geopolymer binder comprises fly ash (FA) and ground granulated blast furnace slag (GGBS), activated by a 12 M NaOH solution. RCA replaced 30% of natural coarse aggregate to form recycled aggregate concrete (RAC), while CS replaced natural fine aggregate in 20% increments up to 100% in RCA based geopolymer concrete to study its effect on compressive, split-tensile, and flexural strengths at ambient (27 °C) and elevated temperatures (100 °C, 300 °C, 500 °C, 700 °C). The experimental findings revealed that integrating CS improved both mechanical and residual thermal properties of RCA-based geopolymer concrete up to 45% and 41%, respectively, over the control mix. The optimal mix exhibited maximum mechanical performance with 30% RCA and 40% CS. This contributes to enhanced fire resistance, sustainability, and reduced dependency on natural resources.